2015 AIChE Spring Meeting & 11th Global Congress on Process Safety : 17th Process Plant Safety Symposium (PPSS) (Center for Chemical Process Safety/AIChE, 2015)
This book is one of the three parallel symposia that comprise the Global Congress on Process Safety. Since its inception in 1992, the Process Plant Safety Symposium has provided perspectives, methods and tools that could be readily practiced at the plant level. The 17th symposium will consist of several sessions, each with up to six 30-minute presentations. --